2013
DOI: 10.1007/s10967-013-2687-4
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of the 131Cs from neutron irradiated barium oxide under microwave radiation

Abstract: In this work, the solubility dependence of radioactive baric samples under influence of microwave radiation (MWR) has been investigated at various concentrations of HCl after irradiation of BaO target at a flux of thermal neutrons. It is established that the use of MWR for dissolution of a sparingly-soluble barium oxide will accelerate a dissolution process at almost an order of magnitude in comparison with usual heating. Each time after separation of the 131Cs from radioactive barium solution analyses on radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Although they provided no discussion/justification, it seems that they ignored the potential interaction between BaO catalyst and MWs that leads to a higher temperature at the catalyst surface compared to the bulk temperature (i.e., hot spot formation). BaO is a non-polar dielectric material with potential defects, including vacancies and interstitials, which couple with MWs to convert its energy into heat (Khujaev et al, 2013). Khujaev et al (Ekinci et al, 2022) reported that the complete dissolution of BaO in hydrochloride acid under MW irradiation at 385 W takes less than 2.5 min, whereas it requires more than 20 min in conventional heating methods, indicating a significant interaction between MWs and BaO.…”
Section: Effect Of Mws Interactions With Polar Molecules and Free Rad...mentioning
confidence: 99%
“…Although they provided no discussion/justification, it seems that they ignored the potential interaction between BaO catalyst and MWs that leads to a higher temperature at the catalyst surface compared to the bulk temperature (i.e., hot spot formation). BaO is a non-polar dielectric material with potential defects, including vacancies and interstitials, which couple with MWs to convert its energy into heat (Khujaev et al, 2013). Khujaev et al (Ekinci et al, 2022) reported that the complete dissolution of BaO in hydrochloride acid under MW irradiation at 385 W takes less than 2.5 min, whereas it requires more than 20 min in conventional heating methods, indicating a significant interaction between MWs and BaO.…”
Section: Effect Of Mws Interactions With Polar Molecules and Free Rad...mentioning
confidence: 99%